HUBUNGAN KADAR KOLESTEROL DAN TEKANAN DARAH PADA KOMUNITAS LANSIA RW IX KELURAHAN SENDANGMULYO KECAMATAN TEMBALANG KOTA SEMARANG - FITRIANI KAHAR; Nurul Qomariyah; Meyriska Frisna Putri (Klinikal Sains : Jurnal Analis Kesehatan, 2022)
Abstract According to Sopiah (2021), hypertension is still the cause of frequent deaths. Physiological and degenerative processes that occur in the elderly can cause changes in cholesterol levels. Hypertensive factors can be caused due to the occurrence of hypercholesterolemia. If a person is affected by hypertension and hypercholesterolemia, it can be dangerous for the health of the elderly. One of the important parameters in assessing the risk of hypertension is total cholesterol. As we get older, most elderly people suffer from cholesterol because the body is no longer able to move freely so that a lot of cholesterol accumulates in the liver, so the elderly need a balance between diet and exercise to avoid excess cholesterol (Susanto, 2010 in Putri, 2016). The purpose of this study is to determine the relationship between cholesterol levels and blood pressure. The benefits of this study are that it can add information to the public about the relationship between cholesterol levels and blood pressure, know the causes and effects of high cholesterol and blood pressure, and can increase self-awareness about the importance of maintaining cholesterol levels and blood pressure. The type of research used was observational which was descriptive and 36 samples were obtained. The results of normal cholesterol levels were obtained by 6 respondents (19.44%) and high cholesterol levels as many as 30 respondents (80.56%), in the results of normal blood pressure there were 24 respondents (66.67%) and high blood pressure as many as 12 respondents (33.33%). The results of the chi-square statistical test can be seen that p-vaue = 0.343 (> 0.05), which means that there is no relationship between cholesterol levels and blood pressure in the elderly community of RW IX Sendangmulyo Village, Tembalang District, Semarang City. The conclusion of this study is that there is no relationship between cholesterol levels and blood pressure. Keywords: Cholesterol Levels, Blood Pressure, Elderly Â© 20xx Universitas Abdurrab